Sternal Closure following Negative Pressure Wound Therapy: A Safe Approach with a New Titanium Device. Issue 3 (March 2014) - Santarpino, Giuseppe; Pollari, Francesco; Fischlein, Theodor J.
Background: The application of negative pressure wound therapy (NPWT) in patients with deep wound infection after cardiac surgery has steadily increased worldwide. Following NPWT, in patients with concomitant sternal diastasis, preparation of the substernal structures for the sternal wires application is mandatory, with increased risk of severe complications, such as laceration of the right ventricle. The aim of this study is to present an innovative technique for sternal closure after NPWT, using the ASCS® System (ASCS atraumatic Sternum Closure System; KS Handelsvertretung Produktinovation, Bad Homburg, Germany). Methods: Between January 2009 and August 2012, 88 patients (mean age 64.2 ± 12.4 years) with deep wound infection and sternal diastasis received NPWT; 16 of these patients (18.2%) underwent sternal closure after NPWT with ASCS®. Results: In all 16 cases, neither sub-sternal dissection nor placement of trans- or peristernal wires was necessary. No damage to the aortocoronary bypass and ventricular rupture occurred. Minimal post-operative bleeding from Redon drains (mean 40 ± 10 ml) was present. At follow-up, deep wound infection and sternal diastasis did not occur. Conclusions: The ASCS® System combined with NPWT in patients with postoperative deep wound infection and sternal diastasis is a feasible and safe procedure. Because preparation of the substernal structures is not necessary, this device might prevent the occurrence of severe complications. Our experience, however, is limited and larger case series are necessary to fully evaluate this new and innovative technique.